Soybeans, Edible—Glycine max (L.) Merr. - James M. Stephens (EDIS)
This document provides an overview of edible soybeans (Glycine max) as a garden vegetable in Florida, highlighting their increasing popularity, nutritional value, and cultivation practices. It describes suitable varieties such as 'Bansei', 'Fuji', 'Verde', and 'Seminole', and offers guidance on planting, harvesting, and usage. Emphasis is placed on harvesting at the mature green stage to avoid disease, and on their versatility as both fresh vegetables and sprouts. Original publication date May 1994.